Orientasi Penyusunan Tafsir Tematik Kementerian Agama Republik Indonesia - Fuad, Asep; Rusmana, Dadan; Rahtikawati, Yayan (Hanifiya: Jurnal Studi Agama-Agama, 2022)
This study aims to discuss the thematic interpretation of the Ministry of Religion of the Republic of Indonesia by the work of a drafting team consisting of interpreters, hadith, and other Islamic sciences who are competent in their respective fields. Characteristics based on this thematic interpretation style is an interpretation whose nuances are social by interpreting the holy verses of the Qur'an using an exclusive theme by collecting verses of the Qur'an from an exclusive theme. This method is relatively new and is considered actual in interpreting the Qur'an. The author will try to reveal a complete understanding of the verses of the Qur'an. With this theory, the interpretation of the Qur'an can be synchronized with an exclusive theme. The research method used in this study is a literature review, which is a series of methods related to collecting library data, reading, taking notes, and studying research materials. The primary source is the thematic interpretation of the work of the Indonesian Ministry of Religion's Pentashihan Mushaf Lajnah. The substance of his research is more about theoretical matters. From there, it is known that the 23 themes of the thematic interpretation of the work of Pentashihan Mushaf Lajnah of the Ministry of Religion of the Republic of Indonesia contain answers to the challenges of the times that are more practical, systematic, moving forward, and very easily understood by the public. The emergence of this thematic interpretation is based on several aspects of the synchronization approach by examining the government's way of multiplying Islamic literature and creating a thematic interpretation that the Indonesian people can understand.